2014
DOI: 10.1111/gcb.12580
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands

Abstract: Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
425
3
6

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 454 publications
(484 citation statements)
references
References 70 publications
50
425
3
6
Order By: Relevance
“…Our correlations support previous findings from various wetland types (as reviewed in Lai, 2009;Olefeldt et al, 2013;Turetsky et al, 2014). The multiple regression analysis of lumped data across Stordalen also showed similar trends to other temperate, boreal or arctic peatlands.…”
Section: Across Peatland Correlates Of C Fluxessupporting
confidence: 89%
“…Our correlations support previous findings from various wetland types (as reviewed in Lai, 2009;Olefeldt et al, 2013;Turetsky et al, 2014). The multiple regression analysis of lumped data across Stordalen also showed similar trends to other temperate, boreal or arctic peatlands.…”
Section: Across Peatland Correlates Of C Fluxessupporting
confidence: 89%
“…As would be expected, the highest emission rates were observed at Torsager after flooding, with rates equivalent to those reported from permanently flooded peatlands (Günther et al, 2013;Kim et al, 1999;Turetsky et al, 2014). Several authors have suggested that CH 4 emissions are insignificant when the GWL is below a certain threshold of 20 to 30 cm below the soil surface (Audet et al, 2013;Koebsch et al, 2013;Shannon and White, 1994).…”
Section: Discussionsupporting
confidence: 61%
“…Variance accounted by the models is reported as the adjusted r 2 when regression relationship was significant. Relevant statistics are shown in text Turetsky et al 2014b). Furthermore, the lower solubility of oxygen as temperature increased (Wilhelm et al 1977) and cessation of radial oxygen loss from the roots following the clearing of the R. taedigera forest exacerbated anaerobic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%